A theoretical investigation of the structural and eletronic properties of orthorhombic CaZrO3 - Rosa, Ieda Lucia Viana; Oliveira, M.C. [UNESP]; Assis, M.; Ferrer, M.; André, R.s.; Longo, Elson; Gurgel, Maria F. C. (Elsevier, 2014)
A CaZrO3 (CZO) powder was prepared by the soft chemical, polymeric precursor method (PPM). The CZO crystalline structure was investigated by powder X-ray diffraction (XDR), Retvield Refinament data, Raman spectra and ultraviolet–visible absorption spectroscopy. A theoretical study was performed using a periodic quantum mechanical calculation (CRYSTAL09 program). The periodic model built for the crystalline CZO structure was consistent with the experimental data obtained from structural and electronic properties. These results show that the material has an orthorhombic structure with experimental and theoretical gap values of 5.7 eV and 6.2 eV, respectively. In this article, we discuss the hybridization process of the oxygen p-orbitals and of the zirconium d-orbitals and analyze their band structures and density of states (partial and total).
Keywords: CaZrO3; theoretical investigation